Estimating Molar Root Volume from Panoramic Radiographs Using a Geometric Approach—An Experimental Method Comparison - Katharina Hartmann; Markus Tröltzsch; Sven Otto; Matthias Tröltzsch (Medicina)
Background and Objectives: Evaluating jaw augmentation procedures usually necessitates pre- and postoperative tomographic imaging. Ethical considerations emphasize minimizing radiation exposure. Given that panoramic radiographs (PR, 2D) offer a lower radiation dose compared to cone-beam CT (CBCT, 3D), this study explores the feasibility of estimating tooth root volume from PR, potentially allowing safer clinical assessments with reduced radiation exposure. Materials and Methods: To develop a mathematical approximation method, the 2D tooth root surface in PR was defined as an elliptical model and a cuboid (3D). The true root volume (mm3) was gathered from CBCTs. The missing link for tooth root volume assessment in 2D radiographs is the depth of the root (vestibulo-oral dimension). It was hypothesized that the tooth root surface and its volume are related. A correlation factor “r” corresponding to the tooth roots’ depths was then calculated. Descriptive and inferential statistics were computed (p < 0.05). Results: The mathematical model was performed on 27 molars with an average volume of 472.83 mm3 (±130.25–CBCT). The factor “r” (obtained by dividing the true root volume from CBCT by the total root surface from PR) was computed as 8.04 (±1.90). Using “r” for the volume calculation in the cuboid model, an average volume of 472.37 (±152.92) for the 27 molars was computed. These volumes did not differ significantly. Conclusions: This study demonstrates that a mathematical model using elliptical projections from panoramic radiographs reliably estimates molar root volume, yielding comparable results to CBCT while reducing radiation exposure.